2021
DOI: 10.3390/ijms222312613
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Chymase-Positive Mast Cells in Recurrent Pleomorphic Adenoma and Carcinoma Ex Pleomorphic Adenoma of the Parotid Gland

Abstract: Incomplete excision of pleomorphic adenoma (PA) may result in recurrent pleomorphic adenoma (RPA). Furthermore, long-term neglected PA may become carcinoma ex pleomorphic adenoma (CXPA). In the present study, the relationships between mast cell-derived chymase and these tumors were examined. The tumor tissues of PA consisted of either or both glandular and fibrotic structures. Histological features of RPA were almost similar to those of PA, except that they showed multinodular structures. CXPA is composed of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In addition, biological and genetic factors may also be considered as potential causes of RPA. [19][20][21] In our cohort, only recurrence times (single/multiple) is an independent prognostic factor for recurrence-free survival of the parotid RPA. It is consistent with previous research.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, biological and genetic factors may also be considered as potential causes of RPA. [19][20][21] In our cohort, only recurrence times (single/multiple) is an independent prognostic factor for recurrence-free survival of the parotid RPA. It is consistent with previous research.…”
Section: Discussionmentioning
confidence: 64%
“…If the benign parotid tumor is near the facial nerve, the tumor must be resected extra‐capsular to preserve the facial nerve, which may result in PA recurrence even after proper superficial parotidectomy or total parotidectomy. In addition, biological and genetic factors may also be considered as potential causes of RPA 19–21 …”
Section: Discussionmentioning
confidence: 99%
“…The role of CAFs in CXPA seems to have been explored only recently. A single study available in the literature using immunolabeling of vimentin and α-SMA showed that CAFs are abundantly present in carcinomatous areas of CXPA ( 79 ). Several clinical trials targeting CAFs are currently active in different tumors, such as head and neck cancer, gastrointestinal carcinoma, hepatocellular carcinoma, breast carcinoma, melanoma, and other solid tumors ( 80 ).…”
Section: Ecm In Pa-cxpa Progressionmentioning
confidence: 99%
“…Immunostaining with the abovementioned antibodies was performed following the protocols described elsewhere [6,42]. In brief, deparaffinized sections were incubated with the respective antibodies overnight at 4 • C, followed by a reaction with components from a labeled streptavidin-biotin peroxidase kit (Dako LSAB kit; Dako, Carpinteria, CA, USA).…”
Section: General Histological and Immunohistological Studiesmentioning
confidence: 99%
“…Recently, research on the relationship between chymase and malignant tumor pathology has attracted a great deal of attention. For example, Kinoshita et al recently reported that the number of chymase-positive mast cells, as well as chymase gene expression, was increased markedly in carcinoma ex pleomorphic adenoma (CXPA) of the parotid gland when compared to the benign parotid tumor, pleomorphic adenoma (PA) [6]. Chymase-positive cells were also significantly increased in human lung and gastric cancers [7,8], indicating the importance of chymase in cancer.…”
Section: Introductionmentioning
confidence: 99%